The Influence of Company Ownership Structure and Earnings Management on Going Concerns Opinion with The Audit Committee as A Moderation Variable in Manufacturing Companies Listed from 2017 to 2022 on the Indonesian Stock Exchange - Andriana, Andriana; Nera Marinda Machdar; Melinda Malau (Fundamental Management Journal, 2024)
This research aims to examine the effect of ownership structure and earnings management on going concerns opinion with the audit committee as a moderating variable. The population in this study are manufacturing companies listed on Bursa Efek Indonesia from 2017-2022. This research uses quantitative research methods with documentation and library techniques. The sampling technique in this research used a purposive sampling approach. The number of samples in this research were 864 observations on 144 companies within 6 years. The analytical method used in this research uses logistic regression analysis with descriptive analysis of data including descriptive statistical test, classic assumption test including goodness of fit test multicollinearity test, overall model fit test and determination test (McFadden R-squared), Moderation Regression Analysis (MRA) and hypothesis testing, namely the partial t test (statistical Z test) with the EViews application tool version 12. The result of this research indicate that partially institutional ownership has a negative effect on going concerns opinion, managerial ownership has no effect on going concerns opinion, earnings management has a negative effect on going concerns opinion, audit committees cannot moderate in weakening or strengthening the influence of institutional ownership structure on going concerns opinion, the audit committee as a moderating variable can strengthen the effect of managerial ownership structure on going concerns opinion, and the audit committee as a moderating variable can weaken the effect of earnings management on going concerns opinion. Keywords: Institutional Ownership, Managerial Ownership, Earning Management, Going Concerns Opinion, Audit Committee